2023
DOI: 10.1101/2023.02.14.528511
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeted protein degradation via intramolecular bivalent glues

Abstract: Targeted protein degradation is a drug modality represented by compounds that recruit a target to an E3 ubiquitin ligase to promote target ubiquitination and proteasomal degradation. Historically, the field distinguishes monovalent degraders from bifunctional degraders (PROTACs) that connect target and ligase via separate binding ligands joined via a linker1-4. Here, we elucidate the mechanism of action of a PROTAC-like degrader of the transcriptional coactivator BRD4, composed of a BRD4 ligand linked to a lig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 80 publications
2
35
0
Order By: Relevance
“…Several recent independent studies with specific protein targets and compounds have also revealed the possibility for converting protein-targeting ligands into molecular glue degraders through subtle chemical changes. These examples include: (1) CR8, a close analog of the nondegradative CDK12 inhibitor (R)- roscovitine, that engages in a ternary complex between CDK12-cyclin K and the CUL4 adaptor protein DDB1, leading to cyclin K ubiquitination and degradation; (2) BI-3802, a BCL6 inhibitor that was discovered to be a degrader of BCL6 through recognition of BI-3802-mediated polymerization filaments by the SIAH1 E3 ligase; (3) GNE-0011, MMH1, and MMH2, reversibly and irreversibly acting analogs of the nondegradative BRD4 inhibitor JQ1, that led to BRD4 degradation through ternary complex formation with the cullin E3 ligase substrate receptor DCAF16. …”
Section: Introductionmentioning
confidence: 99%
“…Several recent independent studies with specific protein targets and compounds have also revealed the possibility for converting protein-targeting ligands into molecular glue degraders through subtle chemical changes. These examples include: (1) CR8, a close analog of the nondegradative CDK12 inhibitor (R)- roscovitine, that engages in a ternary complex between CDK12-cyclin K and the CUL4 adaptor protein DDB1, leading to cyclin K ubiquitination and degradation; (2) BI-3802, a BCL6 inhibitor that was discovered to be a degrader of BCL6 through recognition of BI-3802-mediated polymerization filaments by the SIAH1 E3 ligase; (3) GNE-0011, MMH1, and MMH2, reversibly and irreversibly acting analogs of the nondegradative BRD4 inhibitor JQ1, that led to BRD4 degradation through ternary complex formation with the cullin E3 ligase substrate receptor DCAF16. …”
Section: Introductionmentioning
confidence: 99%
“…In fact, most, if not all of the modalities are still explorative and are at their early stages of development, and caution should be taken before plunging into them, as they may not work solely or at all as intended. For example, multiple PROTAC-like molecules have been reported to work through mechanisms other than those originally anticipated. ,,, …”
Section: Outlook: Opportunities and Challengesmentioning
confidence: 97%
“…Importantly, increasing evidence supports the emerging concept that MG degraders promote pre-existing E3 ligase-target interactions rather than creating new ones de novo. 47,51 interactions are challenging to identify or predict using conventional approaches. We anticipate that the development of novel computational and experimental methods to reveal and validate protein−protein interaction pairs will be fundamental to offer a step change in our ability to discover new MG degraders.…”
Section: Modalitiesmentioning
confidence: 99%
See 2 more Smart Citations